Multinational firms, exclusivity, and the degree of backward linkages - Ping Lin; Kamal Saggi (Deutsche Bundesbank, 2005)
This paper develops a two-tier oligopoly model in which the entry of a multinational firm results in technology transfer to its local suppliers and also impacts the degree of backward linkages in the local industry. The model endogenizes the multinational's choice between anonymous market interaction with its suppliers and contractual relationships with them under which the multinational transfer technology to its suppliers who in turn agree to serve the multinational exclusively. The multinational's entry under an exclusive contract has a de-linking effect that can reduce the degree of competition among suppliers thereby leading to a decline in the level of backward linkages and local welfare. With its emphasis on the supply-side effects of the multinational's entry on local industry, this paper complements existing studies of backward linkages that focus more on demand-side effects.
Keywords: O19; F12; L13; F23; O14; 330; Multinational Firms; Backward Linkages; Vertical Technology Transfer; Exclusivity; Multinationales Unternehmen; Lieferanten-Kunden-Beziehung; Technologietransfer; Markteintritt; Wohlfahrtseffekt; Theorie